Rekonstrukcja technologiczna i badania nieinwazyjne wybranych czerwonych laków organicznych - Mindykowska, Patrycja; Olszewska-Świetlik, Justyna (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2016)
The identification of old organic lake types used in painting techniques is a crucial research issue. Over the centuries, a rich diversity of methods and manners in obtaining organic dyes, including lakes, was utilized for art purposes. In order to fill in the specimen indispensable to precise analysis of art masterpieces, the reconstruction technology of chosen red organic dyes such as: dyer’s madder (Rubia tinctorum L.), red wood of Pernambuco (Caesalpinia crista L.) as well as American cochineal (Dactylopius coccus Costa) was applied. The experiments were conducted based on the set of historical prescriptions (15th– 17th) found in written sources. The attention was shifted towards issues such as: the type of material used and the manner of obtention, which were not neutral for the final colour or properties of obtained lakes. The painting layer was also examined with infrared radiation by means of false colour technique (IRFC). Lakes were mixed with water and resin-oil binder to check how the change of the lake’s colour has been influenced by the binder, the way of coating and the obtention technology.